2017
DOI: 10.1007/s11695-017-2688-4
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life 1 Year After Laparoscopic Sleeve Gastrectomy Versus Laparoscopic Roux-en-Y Gastric Bypass: a Randomized Controlled Trial Focusing on Gastroesophageal Reflux Disease

Abstract: This randomized controlled trial shows that patients who underwent LSG have significantly higher GerdQ scores at both 2 and 12 months postoperatively than patients who underwent LRYGB, whereas overall QOL did not differ significantly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 52 publications
(56 reference statements)
1
54
1
3
Order By: Relevance
“…Specifically, two studies were conducted in each of China, Switzerland, and Greece . One study was conducted in Poland, Finland, Netherland, France, and Brazil . The number of patients undergoing LSG was 544, and 532 patients undergone LRYGB.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, two studies were conducted in each of China, Switzerland, and Greece . One study was conducted in Poland, Finland, Netherland, France, and Brazil . The number of patients undergoing LSG was 544, and 532 patients undergone LRYGB.…”
Section: Resultsmentioning
confidence: 99%
“…Improvement was comparable between LSG and LRYGB, except for physical functioning and general health perception for which RYGB was more beneficial [ 39 ]. In the short-term follow-up (1–2 years), authors report comparable outcomes with significant improvement of QoL after both LSG and LRYGB [ 40 , 41 ]. A study by Takemoto et al reported significant improvement in both mental and physical aspects of QoL 1 year after bariatric procedures, which remained stable during the following 5 years [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, patients' demand is more often in favor of laparoscopic sleeve gastrectomy (LSG), which in the patients' opinion is felt to be associated with lower morbidity, and it does not require long-term vitamins and elemental nutrient supplementation; the cost of which has to be covered by the patients themselves. However, LSG cannot be proposed to obese patients with severe GERD or to sweet eaters, and LRYGB has proven to be an excellent option in these cases [ 23 ]. The first LRYGB in the authors' unit was performed in March 2016, and since then, nine patients have undergone this procedure.…”
Section: Resultsmentioning
confidence: 99%